Carving Arabic Proficiency at Pondok Darut Tauhid PZH Genggong - habibah, habibah; Ali, Hasan (Universitas Islam Zainul Hasan Genggong, 2024)
Pondok Darut Tauhid PZH Genggong, an educational institution that steadfastly makes Arabic language development as one of the main pillars in the intellectual development of its students, is an interesting highlight in this research. Through intensive programs and innovative approaches applied, this boarding school has succeeded in making proud achievements in terms of mastery of Arabic by its students. From the use of communicative methods to the implementation of a strict Arabic-speaking environment, every effort is made to ensure that students master Arabic language skills very well. The findings of this study serve as an example and inspiration for other educational institutions in their efforts to optimize Arabic language learning and realize Arabic language proficiency among their students.